Synthesis and photochemical properties of ruII and ruII-osII complexes with a long bridging ligand of tetrapyridobiphenazine - Siddique, Zainul Abedin (Array, 2008)
Abstract: Semi rigid tetradentate p-conjugated bridging ligand, tetrapyridobiphenazine (tpbpz), its mono and binuclear complexes of ruthenium(II) and ruthenium(II)-osmium(II) have been synthesized. The ligand has chelation sites separated by 2.1 nm. Photochemical properties of these complexes have been investigated using time-resolved laser spectroscopy. In the RuII-OsII heteronuclear complex, intramolecular energy transfer occurs from a metal-to-ligand charge transfer (MLCT) state of the RuII moiety, i.e., (3CT)Ru, to the second metal site, i.e.,OsII. Molar absorption coefficient differences (Dees) along with the excited state formation were determined using an energy transfer method from the triplet metal-to-ligand charge transfer state (3MLCT) of the complex to anthracene. Quantitative conversion of RuII-OsII compound to RuII-OsIII was performed by means of electrochemistry